Comparing of melt blending and solution mixing methods on the physical properties of thermoplastic polyurethane/organoclay nanocomposite films. (July 2017) - Ercan, Nevra; Durmus, Ali; Kaşgöz, Ahmet
In this study, microstructural features and physical properties of thermoplastic polyurethane (TPU)/organoclay nanocomposites films prepared via melt blending (MB) and solution mixing (SM) methods were investigated in detail. Amount of organoclay into the composition varied in the range of 2 and 8 wt%. Microstructural properties of samples were characterized by X-ray diffraction, scanning electron microscopy (SEM), and transmission electron microscopy (TEM) methods. It was found that the organoclay layers exhibited better dispersion, exfoliated, and semi-exfoliated structure in the MB samples than the SM counterparts. Viscoelastic properties of samples were also studied by measuring the rheological behaviors of bulk samples in an oscillatory rheometer in the melt state and measuring of the time-dependent nonlinear creep behaviors of film samples in a dynamic mechanical analyzer in the solid state. Gas and water vapor permeability (WVP) values of nanocomposite films were measured. Based on the melt rheology measurements, it was found that the MB samples showed characteristic solid-like behavior and higher improvement in storage modulus at low-frequency region. Creep behaviors of samples were also quantified with the four-element Burger model. It was found that the introducing of organoclay into the composition via MB method yielded more improvement in the creep resistance, gas, and WVP values of films than the SM counterparts, possibly due to the better dispersion of organoclay layers into the TPU structure. Based on the improvement in permeability and mechanical properties of the samples and also SEM and TEM observations, the average aspect ratio value ( A f ) of organoclay stacks was estimated in the range of 15–20 for the MB samples.